Differentiated Instruction in Practice: Primary Teachers’ Views on the Century of Türkiye Education Model - Tozak, Ezgi; Tamul, Ömer Faruk; Kaşık, Aycan (International Electronic Journal of Elementary Education, 2025)
The aim of this study is to evaluate the differentiated instruction approach implemented at the first-grade level within the scope of the Century of Türkiye Education Model (CTEM), based on the perspectives of primary school teachers. The study examines the classroom reflections of the support and enrichment dimension structured under the CTEM. Designed as a case study, one of the qualitative research designs, the study involved 10 primary school teachers working in public schools during the 2024-2025 academic year, each of whom had at least one student with special educational needs (SEN) in their classroom. The data was collected through semi-structured interviews and analyzed using the descriptive analysis method. The findings were presented within the framework of the following themes: content structure, instructional practices, assessment and evaluation processes, and support and enrichment practices. The teachers stated that they generally viewed the simplification of the content positively; however, they also emphasized that the new arrangements in the Turkish, Life Sciences, and Mathematics curricula have led to some challenges in students’ learning processes. Activity-based approaches were generally supported by the teachers; however, challenges related to the implementation process—such as crowded classrooms and lack of materials—were also highlighted. Although the diversity of assessment and evaluation practices has increased, teachers have pointed out certain limitations regarding time management and ease of implementation. While the theoretical framework for support and enrichment practices appears to be strong, there were deficiencies in implementation support and availability of materials. In conclusion, although the differentiated instruction framework within the CTEM offers an inclusive theoretical structure, the conditions for practical implementation need to be improved. In order to support the implementation of the model, it may be beneficial to provide guidance on differentiated content and offer material support in addition to teacher training. Keywords: Century of Türkiye Education Model, inclusion, differentiation, support, enrichment, students with special educational needs.